Liquid Antennas: Past, Present and Future - Yi Huang; Lei Xing; Chaoyun Song; Stephen Wang; Fatma Elhouni (IEEE Open Journal of Antennas and Propagation)
The liquid antenna, as a new member of the antenna family, has drawn significant and increasing attention from both academia and industry due to its unique features. In this paper, a comprehensive review on this technology is presented which covers both metallic and non-metallic liquid antennas. Non-metallic liquid antennas are further divided into water-based and non-water-based liquid antennas. We first review and compare different liquid antennas and highlight the major developments in the past. Detailed discussions on state-of-the-art designs and current technical challenges are then presented, and finally the ways forward for the future are suggested. As a special feature, an in-depth review and discussion on materials for liquid antennas are provided which was not well covered in the literature in the past, important properties of selected materials are given in three comparison tables which can serve as antenna material selection references. It is shown that Galinstan is probably the best choice for metallic liquid antennas while ionic liquid materials are the preferred choice for dielectric liquid antennas. The challenges of making the liquid antenna for real-world applications are identified and discussed. It is believed that a liquid antenna implemented in radio systems is probably just around the corner.